Comprehensive review on prevalence of caseous lymphadenitis (CLA) in dairy goats: A systematic review and meta-analysis - Nik Danial Asyraf Nik Mustaffa; Chai Min Hian; Yazan Al-Rashdan; Khalid Mahmood Al-Jaff; Mohd Faizal Ghazali; Noor Syaheera Ibrahim (Veterinary Integrative Sciences)
Caseous lymphadenitis (CLA) presents a significant challenge to the dairy goat industry worldwide, negatively affecting animal health, productivity, and economic sustainability. It is a disease caused by Corynebacterium pseudotuberculosis, and its symptoms include the development of abscesses in lymph nodes and other organs. Generally, animals affected by CLA experience reduced milk output, reproductive problems, and higher morbidity and death rates. Furthermore, CLA could harm the well-being of animals by causing pain, discomfort, and disruption of normal behaviours. This review aims to determine the prevalence of CLA cases affecting dairy goats, map the geographical distribution of the disease in dairy goat herds throughout different locations, determine hotspots of CLA incidence and comprehend regional differences. Additionally, the study included relevant information on CLA prevalence in Asia. This comprehensive review is expected to help develop educational strategies for CLA prevention and control among dairy goat farmers. Moreover, an assessment of the economic impact of CLA in dairy goat operations on a global scale was performed. The losses associated with CLA are reduced milk production, lower meat yield, and increased veterinary costs. Besides, the variability of clinical presentation and the limits of conventional diagnostic methods make diagnosing CLA in dairy goats difficult. However, new developments in diagnostics, such as serological testing and polymerase chain reaction (PCR) assays, present chances for early detection and targeted control strategies. Examples of management strategies for CLA in dairy goat herds include vaccination, strict biosecurity protocols, and targeted treatment of infected animals. To surmise, the dairy goat industry can strive to mitigate the effects of CLA and maintain the well-being of dairy goat populations by tackling these challenges and executing comprehensive management strategies.